2020
DOI: 10.1007/s43440-019-00021-0
|View full text |Cite|
|
Sign up to set email alerts
|

The oxidation and hypoglycaemic effect of sorafenib in streptozotocin-induced diabetic rats

Abstract: Background Diabetes reduces the activity of CYP3A4 and may increase the exposure for the drugs metabolized by the isoenzyme. Sorafenib is a multi-targeted tyrosine kinase inhibitor (TKI), used for the treatment of advanced renal cell carcinoma, hepatocellular carcinoma and radioactive iodine resistant thyroid carcinoma. The TKI undergoes CYP3A4-dependent oxidative transformation, which may be influenced by hyperglycaemia. The aim of the study was to compare the oxidation for sorafenib between h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…To properly evaluated our findings, it is important to note the limitations of the conducted studies. First of all, no animal model used in the experiment experienced HCC or T2DM, and as we know from our previous in vivo study with streptozotocin-induced diabetic Wistar rats receiving only sorafenib, T2DM has its impact upon exposure to sorafenib [31]. Additionally, the pharmacokinetic profile of sorafenib, metformin, and atorvastatin may differ between Wistar rats and humans, and the concentrations of sorafenib glucuronide were not measured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To properly evaluated our findings, it is important to note the limitations of the conducted studies. First of all, no animal model used in the experiment experienced HCC or T2DM, and as we know from our previous in vivo study with streptozotocin-induced diabetic Wistar rats receiving only sorafenib, T2DM has its impact upon exposure to sorafenib [31]. Additionally, the pharmacokinetic profile of sorafenib, metformin, and atorvastatin may differ between Wistar rats and humans, and the concentrations of sorafenib glucuronide were not measured.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, since we used non-diabetic rats, this condition did not enhance the exposure to sorafenib and SR_NO [31], and therefore, we were able to examine potential pharmacokinetic DDIs in this animal model.…”
Section: Discussionmentioning
confidence: 99%
“…With long-term treatment, sorafenib can also induce the activity of PXR in HCC cells and the expression of drug-resistant genes, which ultimately leads to multidrug resistance ( 18 ). CYP3A4 is an important regulator of sorafenib metabolism and clearance in HCC cells as it can mediate the oxidative metabolism of sorafenib ( 48 ). Our study identified that a microRNA that can act on the 3’UTR of cyp3a4 : miR-4277.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetics of sorafenib and its metabolites depend on many efflux transporters, such as organic cation transporter−1 (OCT1), organic anion transporting polypeptide 1B1/3 (OATP1B1/3), multidrug resistance-associated protein 2 (MRP2) and protein 3 (MRP3), breast cancer resistance protein (BCRP), and P-glycoprotein (P-pg), which is also an inhibitor [8,9]. Sorafenib has been shown to inhibit P-gp in vitro [3,10] and in vivo [11,12]. After simultaneous administration of sorafenib and P-gp substrates, such as digoxin thereof, the growth of their plasma concentrations cannot be excluded [3,10].…”
Section: Introductionmentioning
confidence: 99%
“…Bearing in mind that sorafenib and probably morphine belong to the P-gp substrates, and sorafenib is also a P-gp inhibitor [10][11][12], the combined use of these drugs may alter their pharmacokinetics, and finally, the safety and efficacy of the cancer therapy. This drug combination in cancer patients may be associated then with drug-drug interactions (DDI) with a higher risk of treatment disruption [42].…”
Section: Introductionmentioning
confidence: 99%